Cooperation visit by Universitas Negeri Malang, Indonesia / Dahlan Abdullah and Johanudin Lahap @ Wahab - Abdullah, Dahlan; Lahap @ Wahab, Johanudin (Faculty of Hotel & Tourism Management, UiTM Pulau Pinang, 2019)
On Tuesday, November 27, 2018, Center of Studies for Hotel and Tourism Management, Universiti Teknologi MARA (UiTM) Pulau Pinang was honoured to host a delegation from from Fakultas Teknik, Universitas Negeri Malang (UM), Indonesia led by its Dean during a collaborative visit by the university. The delegates were welcomed by Rector, several members of UiTM Pulau Pinang’s top management, Head of Center of Studies for Hotel and Tourism Management, program coordinators and several senior officers. Prior to the roundtable discussion, the group was taken for academic tour to visit the Center of Studies’ teaching and learning facilities including commercial kitchen, pastry kitchen, front office and Hotel UiTM rooms. A round table meeting was then organized to discuss the potential collaborative projects between the two establishments.